Prescription of Anticholinergic Drugs in Patients With Schizophrenia: Analysis of Antipsychotic Prescription Patterns and Hospital Characteristics - Hori, Hikaru; Yasui-Furukori, Norio; Hasegawa, Naomi; Iga, Jun-ichi; Ochi, Shinichiro; Ichihashi, Kayo; Furihata, Ryuji; Kyo, Yoshitaka; Takaesu, Yoshikazu; Tsuboi, Takashi; Kodaka, Fumitoshi; Onitsuka, Toshiaki; et al. (Frontiers in Psychiatry, 2022)
In several clinical guidelines for schizophrenia, long-term usage of anticholinergics is not　recommended. We investigated the characteristics of the use of anticholinergics in patients with　schizophrenia by considering psychotropic prescription patterns and differences among hospitals. A cross-sectional, retrospective prescription survey at the time of discharge was conducted on 2027 patients with schizophrenia from 69 Japanese hospitals. We examined the relations among psychotropic drug prescriptions in terms of anticholinergics prescription. We divided the hospitals　into three groups—low rate group (LG), medium rate group (MG), and high rate group (HG)—according to their anticholinergic prescription rates and analyzed the relations between　anticholinergic prescription rates and antipsychotic prescription. Anticholinergic drugs were prescribed to 618 patients (30.5%), and the prescription rates were significantly higher for high antipsychotic doses, antipsychotic polypharmacy, and first-generation antipsychotic (FGA) use. The anticholinergic prescription rate varied considerably among hospitals, ranging from 0% to 66.7%, and it was significantly higher in patients with antipsychotic monotherapy, antipsychotic polypharmacy, and normal and high doses of antipsychotics in HG than in LG and MG. The anticholinergics prescription rate in patients with second-generation antipsychotic monotherapy in HG was also significantly higher than in LG and MG; however, the difference was no longer significant in patients with FGA monotherapy. In conclusion, in addition to high antipsychotic doses, antipsychotic polypharmacy, and FGA use, hospital characteristics influence the prescribing of anticholinergic drugs.